105 Impact of CV Risk Factors/Disease on Length of Stay and Mortality in Patients Presenting with MI. (3rd June 2016) - Loudon, Brodie L; Gollop, Nicholas D; Carter, Paul R; Uppale, Hardeep; Sarma, Jaydeep; Chandran, Suresh; Potluri, Rahul
Abstract : Background: Classical risk factors for cardiovascular disease such as hypertension and diabetes, and their association with myocardial infarction (MI), have been thoroughly investigated. However, more research is needed to investigate the correlation between these risk factors and the impact on length of stay (LOS) and mortality in patients presenting with MI, which was the aim of this study. Methods: We reviewed anonymous patient data including demographics, LOS, prevalence of cardiovascular comorbidities, and mortality during 25, 287 consecutive admissions for MI from seven hospitals in the North West of England between 1 January 2000 and 31 March 2013. The ACALM (Algorithm for Comorbidities, Associations, Length of stay and Mortality) protocol, using ICD-10 and OPCS-4 coding systems, was used to track patient data. LOS and mortality of MI patients with and without cardiovascular comorbidities was compared by multinomial logistic regression. P values <0.05 were taken as statistically significant. Results: Of 25, 287 patients admitted with MI over the study period, mean (± SD) age was 66.6 ± 14.3 and 64.2% were male. The mean (± SD) LOS was 7.0 ± 16.2 days and there were a total of 9, 653 (38.2%) deaths. The classical cardiovascular risk factors hypertension and hyperlipidaemia were associated with a decreased LOS and mortality (7.0 and 4.8 days respectively, P < 0.001; 36.8% OR 0.72 [95% CI 0.67–0.77] and 19.4% OR 0.42 [95% CI 0.39–0.46] respectively, P < 0.001), whereas diabetes was associated with a longer LOS and higher mortality (7.8 days, P < 0.05; 44.4% OR 1.3 [95% CI 1.20–1.41], P < 0.001). Angina pectoris was associated with shorter LOS and reduced mortality (5.4 days; 33.5% OR 0.75 [95% CI 0.68–0.82], P < 0.001). Other concomitant cardiovascular diseases were associated with an increased LOS and mortality: PVD (8.6 days, P < 0.05; 53% OR 1.93 [95% CI 1.68–2.21], P < 0.001), AF (10.9 days; 63.5% OR 1.51 [95% CI 1.38–1.66], P < 0.001), Cerebrovascular disease (15.9 days; 76% OR 2.29 [95% CI 1.67–3.15], P < 0.001), HF (11 days; 69.9% OR 3.28 [95% CI 3.03–3.56], P < 0.001), and IHD (6.7 days, P < 0.001; 38.7% OR 1.16 [95% CI 1.06–1.26], P < 0.05). Conclusion: Cardiovascular risk factors and concomitant disease have a significant impact on LOS and mortality in patients presenting with MI. The presence of these diseases should be used to identify patients at an increased risk of prolonged admissions and death post MI, and services should be directed accordingly.